Tú vales por lo que eres. El espejismo de un cambio en la relación de los niños/jóvenes con madres en reclusión - Díaz Fernández, Adris; Peña Alba, Anahí Elizabeth Peña Alba; Martínez Pérez , Andrea Amanda; Guerra Martínez, Ana Lucía (CALLE14: revista de investigación en el campo del arte, 2021)
The purpose of this article is to identify the mother-child-guardian relationship to improve family bonds. The study was aimed at children/young people 8 to 15 years old whose mothers are imprisoned in Nuevo León, Mexico. This qualitative research used the projective tests “The family” and “Child in the rain” to identify the intimate and unconscious desires of children/young people and their affective needs. A participatory action plan was established through plastic art expressions and an evaluation of their creation and effects. The study concluded that there is no affective bond between children-mother (inmates)-tutor, leaving children/young people with fear, unfulfilled needs, insecurity and low self-esteem. The research shows how art is an ideal way to rediscover situations of attachment, dreams and bewilderment in situations of abandonment, exclusion, as well as an effective means to achieve a change in attitude and behavior.